2004
DOI: 10.1177/001698620404800402
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Development of Perfectionism in Gifted College Students

Abstract: This study is part of a larger research investigation of perfectionism in gifted college students. Employing a qualitative interview design, this study examined factors contributing to the development of two dimensions of perfectionism, socially prescribed and self-oriented, in gifted college students. Findings indicated that exposure to parental perfectionism and an authoritarian parenting style led to the perception of stringent expectations, self-worth tied to achievement, and a fear of disappointing others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(149 citation statements)
references
References 26 publications
6
133
1
9
Order By: Relevance
“…This relationship seems particularly strong when parent and child are of the same gender (Frost, Lahart, & Rosenblate, 1991;Soenens, Elliot, Goossens, Vansteenkiste, Luyten, & Duriez, 2005;Vieth & Trull, 1999). This may indicate that modeling by parents may play a role in the development of positive perfectionism (Hamachek, 1978;Neumeister, 2004), but genetic factors should not be overlooked either as a recent twin study found high heritability values for perfectionistic personal standards (Tozzi et al, 2004). Consequently, a comprehensive developmental analysis of positive perfectionism would also have to take Positive Conceptions of Perfectionism 15 account of the possible interplay between nature and nurture (Collins, Maccoby, Steinberg, Hetherington, & Bornstein, 2000).…”
Section: Developmental Analysismentioning
confidence: 99%
“…This relationship seems particularly strong when parent and child are of the same gender (Frost, Lahart, & Rosenblate, 1991;Soenens, Elliot, Goossens, Vansteenkiste, Luyten, & Duriez, 2005;Vieth & Trull, 1999). This may indicate that modeling by parents may play a role in the development of positive perfectionism (Hamachek, 1978;Neumeister, 2004), but genetic factors should not be overlooked either as a recent twin study found high heritability values for perfectionistic personal standards (Tozzi et al, 2004). Consequently, a comprehensive developmental analysis of positive perfectionism would also have to take Positive Conceptions of Perfectionism 15 account of the possible interplay between nature and nurture (Collins, Maccoby, Steinberg, Hetherington, & Bornstein, 2000).…”
Section: Developmental Analysismentioning
confidence: 99%
“…Speirs-Neumeister (2004) used inductive data analysis to examine what factors contribute to the development of Socially Prescribed and Self-Oriented Perfectionism. Socially Prescribed Perfectionists described being subjected to authoritarian parenting styles and witnessing parental perfectionism.…”
Section: Qualitative Research On Perfectionismmentioning
confidence: 99%
“…Researchers abroad have demonstrated the association between parenting styles and perfectionist tendencies in children (Besharat et al, 2011;Biran & Reese, 2007;Flett & Hewitt, 2002;Kenney-Benson & Pomerantz, 2005). Studies found that there were positive correlations between authoritarian parenting style and negative perfectionism, and also between authoritative parenting style and positive perfectionism (SpeirsNeumeister, 2004). Parenting styles in the West are different to parenting styles practiced in the East (Besharat et al, 2011), therefore there is a need to investigate the roles of parenting styles practiced in Malaysia that predict positive and negative perfectionism among academically gifted students.…”
Section: Problem Statementmentioning
confidence: 99%
“…Meanwhile, the authoritative parent attempts to direct the child's activities but in a rational, issue-oriented manner. Researches have demonstrated the association between parenting styles and perfectionist tendencies in children (Besharat et al, 2011;Kawamura, Frost, & Harmatz, 2002;SpeirsNeumeister, 2004). Positive perfectionist characteristics have proven to be associated with harsh and authoritarian parenting styles (Kawamura et al, 2002), and father's authoritarian style was significantly associated with dimensions perfectionism in their children (Besharat et al, 2011).…”
Section: Parenting Styles and Perfectionismmentioning
confidence: 99%